Early Childhood Education Teacher Management Strategy in Preventing Verbal Bullying in Early Childhood - Ali Masykuri; Milla Ahmadia Apologia; Shofiyatuz Zahroh; Rif'atul Anita; Ganal Arief Rahmawan; Tantri Risda Zubaidah (Al-Qalam Institue, 2025)
Early childhood is a critical stage for character formation and socio-emotional development, making children vulnerable to deviant behaviors such as verbal bullying. This study aims to identify and analyze teacher management strategies in Islamic Early Childhood Education (PIAUD) to prevent verbal bullying in the classroom through Islamic values. This research employed a qualitative phenomenological design, using in-depth interviews, participatory observations, and documentation with PIAUD teachers experienced in handling verbal bullying. The findings reveal three main strategies: internalizing Islamic values through storytelling and routine practices; humanistic classroom management based on compassion and positive communication; and active collaboration with parents and school institutions. These strategies effectively raise children’s verbal awareness, build social leadership, and reduce verbal bullying behavior across genders. The study concludes that value-based teacher management is a constructive and preventive approach to fostering a safe, inclusive, and character-driven learning environment. These findings have practical implications for developing teacher training programs and Islamic early childhood education policies grounded in moral and spiritual values.